Synthesis of Strontium Substituted Hydroxyapatite Coating on Titanium Via Hydrothermal Method - Tam, Le Thi; Kien, Vu Dao; Tuan, Ta Quoc; Van Toan, Le; Phuong, Pham Thai Mai; Hung Vuong, Pham (VNU Journal of Science: Mathematics - Physics; Vol 40 No 3DO - 10.25073/2588-1124/vnumap.4906, 2024)
In this work, Strontium substituted hydroxyapatite (SrHA) coatings were successfully deposited onto etched titanium substrates in solutions of H 2 SO 4 and HCl. The deposition was achieved by hydrothermal method by immersing the substrates in a solution containing Ca(NO 3 ) 2 .4H 2 O, NH 4 H 2 PO 4 , and 5% Sr(NO 3 ) 2 , followed by heating at 200°C for 12 hours. X-ray diffraction (XRD) analysis confirmed that all SrHA coatings exhibited a crystalline hydroxyapatite structure. Field-emission scanning electron microscopy (FE-SEM) revealed that the SrHA coatings exhibited microstructure. The reults of testing Bioactivity and in vitro biocompatibility of the SrHA-coated titanium substrates using SBF solution and baby hamster kidney (BHK) cells showed good biological properties of the SrHA coatings.